Renewable energy policies in federal government systems - Jasper Meya; Paul Neetzow (University of Oldenburg, Department of Economics, 2019)
Renewable energy (RE) policies are widely used to decarbonize power generation and implemented at various governance levels. We use an analytically tractable two-level model to study the effects of overlapping RE policies from the federal and state governments. We find that there are contrasting incentives for states to support RE deployment, depending on whether the federal government implements a feed-in tariff (FIT) or an auction system. Under federal FIT, states that bear a greater burden in financing the federal policy under-subsidize RE in order to reduce nationwide RE deployment and thereby lower their costs. Under federal auction, states that bear a greater burden to finance federal policy oversubsidize RE to drive down the quota price, and thereby also their costs. In an application to Germany, we illustrate that the recent shift from FIT to auctions increases incentives for state governments to support RE in the demand-intensive south, while decreasing them in the wind-abundant north.
Keywords: D47; Q42; Q48; 330; auction; feed-in tariff; multi-level governance; fiscal federalism; overlapping regulation; energy transition